Optimalisasi Edukasi Kesehatan Ibu untuk Meningkatkan Kepatuhan Pemberian ASI di Desa Sukamulya - Nurkholik, Dadeng; Rohita, Tita; Zulfa, Ira; Rahayu, Fadila; Sari, Bunga Puspita; Dwi, Adinda (Yayasan Inspirasi El Burhani, 2024)
Background: Exclusive breastfeeding during the first six months of life is an important effort to improve the health and development of babies. Objective: This aims to optimize maternal health knowledge in Sukamulya Village in order to increase their compliance with breastfeeding. Method: This service program involves several main activities: (1) Health Education: Holding training sessions and seminars regarding the benefits and techniques of breastfeeding for mothers in the village. Education is carried out by medical personnel and nutritionists. (2) Individual Counseling: Providing personal consultations for mothers who experience difficulties or have questions regarding breastfeeding. (3) Providing educational materials: Distributing brochures, posters and practical guides on exclusive breastfeeding to mothers in Sukamulya Village. Results: After program implementation, maternal health knowledge regarding breastfeeding has increased significantly. Data shows that adherence to breastfeeding increased from 45% before the intervention to 75% after the program was implemented. Feedback from participants shows an increase in understanding and application of breastfeeding practices in their daily lives. Conclusion: Optimizing maternal health knowledge through education and counseling is effective in increasing compliance with breastfeeding in Sukamulya Village. This program shows that a knowledge-based approach can improve awareness and practice of breastfeeding, contributing to the health and well-being of babies. Recommendations for further program development include sustainable implementation and strengthening community support.